A Feasibility Study of Applying Laser Line Scanning to AUV Hydrodynamic Parameter Identification. (30th April 2018) - Chou, Yu-Cheng; Nakajima, Madoka; Chen, Hsin-Hung
Abstract : Precise control is a key factor in enabling Unmanned Underwater Vehicles (UUVs) to complete various underwater activities. The development of UUV control rules is mostly based on UUV dynamic models. However, such dynamic models contain unknown hydrodynamic parameters that need to be identified. This paper presents a new method, Laser Line Scanning for Hydrodynamic Parameter Identification (LSHPI), which integrates laser line scanning, decoupled dynamics, and evolutionary optimisation to identify the hydrodynamic parameters of an Autonomous Underwater Vehicle (AUV). In this research, laser images, seen from an on board camera's perspective and created using Open Graphics Library (OpenGL), were used to validate LSHPI's feasibility. The accuracy of the AUV positions and Euler angles obtained by the laser image-based methods were investigated for each decoupled One-Dimensional (1D) motion and the influence of other motion disturbances on the accuracy of the obtained AUV positions or Euler angles was also evaluated. In addition, the accuracy of the surge-related hydrodynamic parameters obtained by LSHPI was investigated under different motion disturbances. Based on the hydrodynamic parameter identification results under different motion disturbances, LSHPI's feasibility was successfully validated.